Early diabetes - Camerini-Davalos, Rafael A.; Cole, Harold S. (Advances in metabolic disorders. Supplement, 1970)
Advances in Metabolic Disorders, Supplement 1: Early Diabetes covers the discussions during the first International Symposium on Early Diabetes. The book discusses the views of the role of genetic factors in diabetes; the genetic problem posed by the relatively high frequency of diabetes; the relationship between diabetes and prediabetes in the mother; and the congenital defect in the offspring. The text also describes the report on the genetics of diabetes among the Pima Indians, as well as the genetics of animals with spontaneous diabetes. The pathophysiology of diabetes mellitus, the conce.